Understanding Tourists’ Motivation in Virtual Tour - Kenyo Kharisma Kurniasari; Jati Paras Ayu; Vitha Octavanny (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
In recent years, the rapid growth of virtual technology has penetrated the tourism industry, and the pandemic has boosted its tremendous growth worldwide, including in Indonesia. Travel restrictions due to prevention strategies during the COVID-19 pandemic have been responsible for increasing the demand for virtual tours and creating a niche market in tourism, rather than only being a tool for promotional marketing. It is deemed important to understand the market in order to develop a sustainable market in this sector successfully. Therefore, this study examined the motivations of virtual tourists and determined whether virtual tour experiences can influence their motivation to visit the destination. First, a quantitative research method using factor analysis with a total of 111 (n) completed questionnaires was performed. Then, with content analysis, the descriptive representation of the content was established to support the factor dimension. This study found that there were five factors of the main motivations for tourists to do virtual tour activities. They are “Relaxing & well-being”, “Novelty”, “Education & Learning”, “Tendency to visit the destination”, and “Digital experience”. Furthermore, this study found that the real physical travel experience is irreplaceable, but virtual tour brings new & unique experience to tourists. The results of this research can be implemented by the tourism business to enhance the understanding and development of the future of virtual tours experience in the tourism industry. It can also contribute to the current knowledge of digital tourism applications, particularly in Indonesia’s context.